2005
DOI: 10.1111/j.1469-7610.2005.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a typology of specific language impairment

Abstract: The language problems that emerged from the two samples of children with SLI could be described as falling into four types. Based on these language types, four subgroups of children with SLI could be distinguished, each with a specific profile. Some subgroups had severe problems on one specific type of language problem; others had severe problems in more than one type of language problem when compared to the other subgroups of the same age sample. The different profiles may indicate that a more dynamic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 31 publications
6
34
0
3
Order By: Relevance
“…In this study 26 tests differentiated children with SLI from matched control children at the group level. Furthermore, the language deficits of children with SLI in Finnish that were found in this study are consistent with those found in international studies [7,8,16,17]. On a local basis, the result increases the clinicians' confidence, both physicians' and SLTs', in language tests even in the case of smaller populations with their own languages, such as Finnish.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study 26 tests differentiated children with SLI from matched control children at the group level. Furthermore, the language deficits of children with SLI in Finnish that were found in this study are consistent with those found in international studies [7,8,16,17]. On a local basis, the result increases the clinicians' confidence, both physicians' and SLTs', in language tests even in the case of smaller populations with their own languages, such as Finnish.…”
Section: Discussionsupporting
confidence: 79%
“…Most of the test procedures used to identify and describe subgroups of language impairments are standardized either in English or in the language of one country only [4,15,16]. Smaller populations with their own languages, such as Finnish, may only have indicative norms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, monolingual children with PLI present a wide range of variation in language profiles and symptom severity (e.g. van Weerdenburg, Verhoeven, & van Balkom, 2006). As such it is quite expected the profiles of two bilingual children with PLI would differ substantially, despite both children meeting the same study criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Clusters 1, 2, and 6 have a pattern of low sentence recall compared to stronger and similar word and nonword reading efficiency and math fluency. These clusters (1,2,6) are distinguished by overall performance (low, average, high, respectively). Clusters 3 and 4 show the opposite pattern with stronger sentence recall performance compared to reading and math performance.…”
Section: Resultsmentioning
confidence: 99%